Values Education in Higher Education - Miriam Iglesias León; Manuel Cortés Cortés; Norma Mur Villar; Coralia Perez Maya; María José Aguilar Cordero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Present times are characterized by dramatic changes in different areas of life. Twenty-first century professionals need a special training that enables them to venture into various branches of knowledge. Therefore, they must have an original thinking and innovation skills; they must be part of their training, take a dignified position in the social context they live in and be committed to its mission. The University, as a social institution, should include in their training models social problems and transformation processes, so that students learn and teachers teach with true meaning and significance. At university level, values education is centered in the practical teaching-learning process and is based on study and work. This problem needs to be analyzed from a specific historical approach on subject-object relationship. This work is aimed at socializing some theoretical and practical reflections on values education at the university as well as teacher's role in their formation from an instructive perspective.